The Host Protein Reticulon 3.1A Is Utilized by Flaviviruses to Facilitate Membrane Remodelling - Simmons, Cameron (2018)
Flaviviruses are enveloped, positive-sensed single-stranded RNA viruses that remodel host membranes, incorporating both viral and host factors facilitating viral replication. In this study, we identified a key role for the membrane-bending host protein Reticulon 3.1 (RTN3.1A) during the replication cycle of three flaviviruses: West Nile virus (WNV), Dengue virus (DENV), and Zika virus (ZIKV). We observed that, during infection, RTN3.1A is redistributed and recruited to the viral replication complex, a recruitment facilitated via the WNV NS4A protein, however, not DENV or ZIKV NS4A. Critically, small interfering RNA (siRNA)-mediated knockdown of RTN3.1A expression attenuated WNV, DENV, and ZIKV replication and severely affected the stability and abundance of the NS4A protein, coinciding with a significant alternation and reduction of viral membrane structures in the endoplasmic reticulum. These observations identified a crucial role of RTN3.1A for the viral remodelling of host membranes during efficient flavivirus replication and the stabilization of viral proteins within the endoplasmic reticulum.